An Institutional Approach to Developing Research Data Management Infrastructure - James A. J. Wilson; Luis Martinez-Uribe; Michael A. Fraser; Paul Jeffreys (International Journal of Digital Curation, 2011)
This article outlines the work that the University of Oxford is undertaking to implement a coordinated data management infrastructure. The rationale for the approach being taken by Oxford is presented, with particular attention paid to the role of each service division. This is followed by a consideration of the relative advantages and disadvantages of institutional data repositories, as opposed to national or international data centres. The article then focuses on two ongoing JISC-funded projects, ‘Embedding Institutional Data Curation Services in Research’ (Eidcsr) and ‘Supporting Data Management Infrastructure for the Humanities’ (Sudamih). Both projects are intra-institutional collaborations and involve working with researchers to develop particular aspects of infrastructure, including: University policy, systems for the preservation and documentation of research data, training and support, software tools for the visualisation of large images, and creating and sharing databases via the Web (Database as a Service).